Discrete transfer method for radiative transfer in regular one-dimensional isotropically scattering variable index media-part II: Concentric-Spherical geometry - A. Dehghanian; S.M. Hosseini Sarvari (Case Studies in Thermal Engineering)
This research investigates steady and transient radiative heat transfer in a one-dimensional concentric spherical medium characterized by a spatially variable refractive index. The discrete transfer method is applied, with the solution domain confined to symmetric boundaries. Radiative transfer is modeled in a spherical annulus sector with specular sidewall reflectivity. The spatial and angular domains are divided into annular volume elements and solid angles, respectively. To enhance computational efficiency, an optimized discrete ray tracing technique is implemented. The research examines media that absorb, emit, and scatter radiation isotropically, considering various radial refractive index distributions for both steady and transient cases. Numerical examples illustrate the influence of radiative properties, and comparisons with other methods highlight the proposed approach's accuracy and reduced computational cost.